Walking-Writing-Weaving: An A/r/tographic Reconsideration of the Human-Algorithm Relationship - Moylan, Rachel (Art/Research International)

(untitled) (University of Alberta, 2024)
Internet algorithms influence the news we read, the products we buy, the music we listen to, the people we interact with, and even the words we use to communicate. Our preferences, beliefs, perceptions, and behaviours are all shaped by algorithmic processes, threatening our capacities for self-awareness and self-formation. What’s more, algorithms operate smoothly and imperceptibly under the surface of our postdigital existence. How can we begin to make sense of our relationships with algorithms, knowing that they operate beyond the limits of perception? How can we reconsider the human-algorithm relationship as a way of opening new possibilities of being? Using a/r/tographic inquiry, I addressed these questions through a months-long process of walking, writing, and weaving, revealing insights that may help illuminate a path toward living with the complexities and contradictions while hanging on to the parts of ourselves that remain resistant to domination.